Mixed-Methods Analysis of Emotional Quality in Sports Organizations: Facial Expressions of Child Users of Sports Services as Data - Morales-Sánchez, Verónica; Pérez-López, Rocío; Reigal, Rafael E.; Hernández-Mendo, Antonio (Frontiers in Psychology, 2020)
Proper quality management of sports services requires knowledge of the needs, perceptions, expectations, and emotions of users. Facial expressions provide relevant information about the immediate perception of stimuli. The objective of this study was therefore to analyze how a group of child users of sports services expressed their satisfaction with the programs in which they participated through facial expressions during an in-depth interview tailored to their age. Nineteen child users of a sports organization (aged from 5 to 12 years) were interviewed, involving both qualitative and quantitative analyses. The analysis of facial expressions was performed using Face Reader v.6.1.10, which automatically analyzes eight categories of facial expressions (six basic emotions, one neutral and one unidentified). The data collection and transformation procedures fully satisfied the requirement for flexibility and provide new perspectives for incorporating data into the study of biopsychosocial factors in everyday contexts using a Mixed-Methods approach. In addition, the generalizability analysis itself, carried out to determine the levels of reliability, generalizability and precision of the sample (with relative and absolute G indexes of between .86 and .93 for the three analyses performed), was also a Mixed-Methods procedure.